Effective Learning Strategies Through Films to Improve Listening Skills in Madarasah Aliyah - Shobrina, Desy Hidayah; Na’imah, Na’imah; Irwansyah, Moh (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2024)
Learning media has recently developed very well in various types, one of which is media to improve listening skills. One example of media that can be used is English language films. By using this film media, many benefits can be obtained, namely being able to learn good English pronunciation directly from the films shown, being able to add new vocabulary, being able to learn good and correct grammar, and also being able to practice listening skills. The purpose of this study was to determine the strategy for the success of using films to improve listening skills and the perspectives of MAN 1 Yogyakarta students on the use of films as learning media. The method used in this study is qualitative research. This type of research is descriptive-qualitative research. Data collection techniques include interviews and documentation. Data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. Based on the results of the research that has been done, it can be concluded that: 1) with the method of listening to films in English, students can easily understand English pronunciation and also enrich vocabulary, 2) successfully improve concentration skills in learning, 3) make it easier for students to understand English through audio visuals.